Preparation method of high-capacity natural graphite-based negative electrode material

By mixing natural graphite with a single carbon nanotuba, nano -titanium dioxide, asphalt coke microfream, and pre -carbonization and carbonization treatment, the problem of low capacity of the existing natural graphite base material is Chemical reaction performance.

CN119349570APending Publication Date: 2025-01-24LUOBEI AOXING NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411482058.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The theoretical capacity of existing natural graphite-based negative electrode materials is relatively low, which limits the improvement of the overall capacity of lithium batteries.

Method used

The method of preparation of high -capacity natural graphite base negative materials is used to mix natural graphite and single -wall carbon nanotubes, nano -titanium dioxide, asphalt coke microfiflo, and perform pre -carbonization and carbonization.

Benefits of technology

It improves the conductivity and electrochemical reaction performance of the negative electrode material, reduces the impedance of the battery, and enhances the overall performance of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005097667490000081
    Figure BDA0005097667490000081
  • Figure BDA0005097667490000091
    Figure BDA0005097667490000091
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-capacity natural graphite-based negative electrode material, and the preparation method comprises the following steps: A, adding natural graphite into a crusher for crushing processing, and then sieving to obtain graphite powder; b, mixing graphite powder with single-walled carbon nanotubes, nano titanium dioxide and pitch coke micro powder, and immersing the mixture into an ethanol solution for stirring and mixing; c, completely evaporating the solvent to obtain a mixture; d, the mixture is added into a carbonization furnace, then pre-carbonization is conducted through inert gas, the pre-carbonization temperature ranges from 1200 DEG C to 1300 DEG C, the pre-carbonization time ranges from 2 h to 3 h, and a pre-carbonization product is obtained after pre-carbonization is completed; e, the pre-carbonization product is heated and carbonized, inert gas protection is adopted, and a carbonization product is obtained after carbonization is finished; and F, cooling the carbonized product to obtain the graphite-based negative electrode material. The preparation method adopted by the invention is simple to operate, the prepared negative electrode material is good in conductivity, the impedance of the battery is reduced, and the conductivity and electrochemical reaction performance of the product are effectively enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of negative electrode material preparation, and in particular to a method for preparing a high-capacity natural graphite-based negative electrode material. Background Art

[0002] Natural graphite lithium battery negative electrode material has high capacity, about 10-20% higher than ordinary carbon materials; the cost of manufacturing negative electrode materials is low, because it is an ideal graphite crystal structure, and does not require a high-temperature graphitization process; natural graphite is a dominant mineral in my country, with reserves accounting for about 70% of the world; natural graphite processing technology is mature, and all processing production lines are independently manufactured. At present, carbon materials are the dominant materials for lithium battery negative electrode materials. For a considerable period of development, carbon materials are indispensable, and natural graphite negative electrode materials account for 55% of the entire market. This trend will further increase the proportion of natural graphite-based negative electrode materials as the scale of lithium battery production expands, and demand will also increase accordingly.

[0003] The negative electrode material is one of the most important factors affecting the battery capacity and cycle performance. Currently, the most mature negative electrode material is graphite material, including natural graphite, artificial graphite, etc. The graphite structure is stable and has a stable reversible capacity during the charge and discharge cycle. However, the low theoretical capacity of the graphite negative electrode greatly limits the improvement of the overall capacity of the battery. Therefore, it is necessary to make improvements. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing a high-capacity natural graphite-based negative electrode material to solve the problems raised in the above-mentioned background technology.

[0005] To achieve the above object, the present invention provides the following technical solution: a method for preparing a high-capacity natural graphite-based negative electrode material, the preparation method comprising the following steps:

[0006] A. Add natural graphite into a pulverizer for pulverization and then sieve to obtain graphite powder;

[0007] B. Mixing graphite powder with single-walled carbon nanotubes, nano-titanium dioxide and asphalt coke micropowder, immersing in an ethanol solution and stirring to mix;

[0008] C. Then, the solvent is completely evaporated to obtain a mixture;

[0009] D. Add the mixture into a carbonization furnace, and then pass an inert gas to perform pre-carbonization, and obtain a pre-carbonized product after the pre-carbonization is completed;

[0010] E. Carbonizing the pre-carbonized product after heating and protecting it with inert gas to obtain a carbonized product after the carbonization is completed;

[0011] F. After cooling the carbonized product, a graphite-based negative electrode material is obtained.

[0012] Preferably, the raw material components include 50-80 parts by weight of natural graphite, 5-10 parts of single-walled carbon nanotubes, 4-8 parts of nano-titanium dioxide, and 10-20 parts of asphalt coke powder.

[0013] Preferably, in step A, the speed of the pulverizer is 200-600 rpm, and the pulverizing time is 50 min-70 min.

[0014] Preferably, the particle size D50 of the natural graphite after sieving in step A is 15-20 microns, and the tap density is 0.55-0.75 g / cm 3 .

[0015] Preferably, in step B, the stirring mixing rate is 300-600 rpm, and the mixing time is 20 min-40 min.

[0016] Preferably, in step D, the pre-carbonization temperature is 700-800° C. and the time is 1 h-2 h.

[0017] Preferably, in step E, the pre-carbonization temperature is 1200-1300° C. and the time is 2 h-4 h.

[0018] Preferably, the inert gas introduced in step D is argon, the argon introduction flow rate is 20-30 L / h, and the introduction time is 50 min-70 min.

[0019] Preferably, the inert gas introduced in step E is argon, the argon introduction flow rate is 30-40 L / h, and the introduction time is 90 min-130 min.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] (1) The preparation method adopted by the present invention is simple to operate, and the obtained negative electrode material has good conductivity, reduces the impedance of the battery, and effectively enhances the conductivity and electrochemical reaction performance of the product.

[0022] (2) The present invention performs pre-carbonization before carbonization, which can effectively prevent the particle powder from agglomerating due to adhesion and affecting the processing quality of the negative electrode material.

[0023] (3) In the present invention, argon gas is introduced during both the pre-carbonization and carbonization processes, which can solve the radial and axial segregation problems of the material during the solidification process and improve the processing quality of the negative electrode material. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Embodiment 1:

[0026] The present invention provides the following technical solution: a method for preparing a high-capacity natural graphite-based negative electrode material, the preparation method comprising the following steps:

[0027] A. Add natural graphite into a pulverizer for pulverization and then sieve to obtain graphite powder;

[0028] B. Mixing graphite powder with single-walled carbon nanotubes, nano-titanium dioxide and asphalt coke micropowder, immersing in an ethanol solution and stirring to mix;

[0029] C. Then, the solvent is completely evaporated to obtain a mixture;

[0030] D. Add the mixture into a carbonization furnace, and then pass an inert gas to perform pre-carbonization, and obtain a pre-carbonized product after the pre-carbonization is completed;

[0031] E. Carbonizing the pre-carbonized product after heating and protecting it with inert gas to obtain a carbonized product after the carbonization is completed;

[0032] F. After cooling the carbonized product, a graphite-based negative electrode material is obtained.

[0033] In this embodiment, the raw material components include 50 parts of natural graphite, 5 parts of single-walled carbon nanotubes, 4 parts of nano-titanium dioxide, and 10 parts of asphalt coke powder by weight.

[0034] In this embodiment, the speed of the pulverizer in step A is 200 rpm and the pulverizing time is 50 min.

[0035] In this embodiment, the particle size D50 of the natural graphite after sieving in step A is 15 microns, and the tap density is 0.55 g / cm 3 .

[0036] In this embodiment, the stirring and mixing rate in step B is 300 rpm and the mixing time is 20 min.

[0037] In this embodiment, the pre-carbonization temperature in step D is 700° C. and the time is 1 hour.

[0038] In this embodiment, the pre-carbonization temperature in step E is 1200° C. and the time is 2 hours.

[0039] In this embodiment, the inert gas introduced in step D is argon, the argon introduction flow rate is 20 L / h, and the introduction time is 50 min.

[0040] In this embodiment, the inert gas introduced in step E is argon, the argon introduction flow rate is 30 L / h, and the introduction time is 90 min.

[0041] Embodiment 2:

[0042] A method for preparing a high-capacity natural graphite-based negative electrode material, the preparation method comprising the following steps:

[0043] A. Add natural graphite into a pulverizer for pulverization and then sieve to obtain graphite powder;

[0044] B. Mixing graphite powder with single-walled carbon nanotubes, nano-titanium dioxide and asphalt coke micropowder, immersing in an ethanol solution and stirring to mix;

[0045] C. Then, the solvent is completely evaporated to obtain a mixture;

[0046] D. Add the mixture into a carbonization furnace, and then pass an inert gas to perform pre-carbonization, and obtain a pre-carbonized product after the pre-carbonization is completed;

[0047] E. Carbonizing the pre-carbonized product after heating and protecting it with inert gas to obtain a carbonized product after the carbonization is completed;

[0048] F. After cooling the carbonized product, a graphite-based negative electrode material is obtained.

[0049] In this embodiment, the raw material components include 80 parts of natural graphite, 10 parts of single-walled carbon nanotubes, 8 parts of nano-titanium dioxide, and 20 parts of asphalt coke powder by weight.

[0050] In this embodiment, the speed of the pulverizer in step A is 600 rpm and the pulverizing time is 70 min.

[0051] In this embodiment, the particle size D50 of the natural graphite after sieving in step A is 20 microns, and the tap density is 0.75 g / cm 3 .

[0052] In this embodiment, the stirring and mixing rate in step B is 600 rpm and the mixing time is 40 min.

[0053] In this embodiment, the pre-carbonization temperature in step D is 800° C. and the time is 2 h.

[0054] In this embodiment, the pre-carbonization temperature in step E is 1300° C. and the time is 4 hours.

[0055] In this embodiment, the inert gas introduced in step D is argon, the argon introduction flow rate is 30 L / h, and the introduction time is 70 min.

[0056] In this embodiment, the inert gas introduced in step E is argon, the argon introduction flow rate is 40 L / h, and the introduction time is 130 min.

[0057] Embodiment three:

[0058] A method for preparing a high-capacity natural graphite-based negative electrode material, the preparation method comprising the following steps:

[0059] A. Add natural graphite into a pulverizer for pulverization and then sieve to obtain graphite powder;

[0060] B. Mixing graphite powder with single-walled carbon nanotubes, nano-titanium dioxide and asphalt coke micropowder, immersing in an ethanol solution and stirring to mix;

[0061] C. Then, the solvent is completely evaporated to obtain a mixture;

[0062] D. Add the mixture into a carbonization furnace, and then pass an inert gas to perform pre-carbonization, and obtain a pre-carbonized product after the pre-carbonization is completed;

[0063] E. Carbonizing the pre-carbonized product after heating and protecting it with inert gas to obtain a carbonized product after the carbonization is completed;

[0064] F. After cooling the carbonized product, a graphite-based negative electrode material is obtained.

[0065] In this embodiment, the raw material components include 55 parts of natural graphite, 6 parts of single-walled carbon nanotubes, 5 parts of nano-titanium dioxide, and 12 parts of asphalt coke powder by weight.

[0066] In this embodiment, the speed of the pulverizer in step A is 300 rpm and the pulverizing time is 55 min.

[0067] In this embodiment, the particle size D50 of the natural graphite after sieving in step A is 16 microns, and the tap density is 0.58 g / cm 3 .

[0068] In this embodiment, the stirring and mixing rate in step B is 350 rpm and the mixing time is 25 min.

[0069] In this embodiment, the pre-carbonization temperature in step D is 720° C. and the time is 1 hour.

[0070] In this embodiment, the pre-carbonization temperature in step E is 1240° C. and the time is 2 hours.

[0071] In this embodiment, the inert gas introduced in step D is argon, the argon introduction flow rate is 22 L / h, and the introduction time is 55 min.

[0072] In this embodiment, the inert gas introduced in step E is argon, the argon introduction flow rate is 32 L / h, and the introduction time is 95 min.

[0073] Embodiment 4:

[0074] A method for preparing a high-capacity natural graphite-based negative electrode material, the preparation method comprising the following steps:

[0075] A. Add natural graphite into a pulverizer for pulverization and then sieve to obtain graphite powder;

[0076] B. Mixing graphite powder with single-walled carbon nanotubes, nano-titanium dioxide and asphalt coke micropowder, immersing in an ethanol solution and stirring to mix;

[0077] C. Then, the solvent is completely evaporated to obtain a mixture;

[0078] D. Add the mixture into a carbonization furnace, and then pass an inert gas to perform pre-carbonization, and obtain a pre-carbonized product after the pre-carbonization is completed;

[0079] E. Carbonizing the pre-carbonized product after heating and protecting it with inert gas to obtain a carbonized product after the carbonization is completed;

[0080] F. After cooling the carbonized product, a graphite-based negative electrode material is obtained.

[0081] In this embodiment, the raw material components include 75 parts of natural graphite, 8 parts of single-walled carbon nanotubes, 7 parts of nano-titanium dioxide, and 18 parts of asphalt coke powder by weight.

[0082] In this embodiment, the speed of the pulverizer in step A is 500 rpm and the pulverizing time is 65 min.

[0083] In this embodiment, the particle size D50 of the natural graphite after sieving in step A is 18 microns, and the tap density is 0.70 g / cm 3 .

[0084] In this embodiment, the stirring and mixing rate in step B is 550 rpm and the mixing time is 38 min.

[0085] In this embodiment, the pre-carbonization temperature in step D is 780° C. and the time is 2 h.

[0086] In this embodiment, the pre-carbonization temperature in step E is 1280° C. and the time is 4 hours.

[0087] In this embodiment, the inert gas introduced in step D is argon, the argon introduction flow rate is 28 L / h, and the introduction time is 65 min.

[0088] In this embodiment, the inert gas introduced in step E is argon, the argon introduction flow rate is 38 L / h, and the introduction time is 120 min.

[0089] Embodiment five:

[0090] A method for preparing a high-capacity natural graphite-based negative electrode material, the preparation method comprising the following steps:

[0091] A. Add natural graphite into a pulverizer for pulverization and then sieve to obtain graphite powder;

[0092] B. Mixing graphite powder with single-walled carbon nanotubes, nano-titanium dioxide and asphalt coke micropowder, immersing in an ethanol solution and stirring to mix;

[0093] C. Then, the solvent is completely evaporated to obtain a mixture;

[0094] D. Add the mixture into a carbonization furnace, and then pass an inert gas to perform pre-carbonization, and obtain a pre-carbonized product after the pre-carbonization is completed;

[0095] E. Carbonizing the pre-carbonized product after heating and protecting it with inert gas to obtain a carbonized product after the carbonization is completed;

[0096] F. After cooling the carbonized product, a graphite-based negative electrode material is obtained.

[0097] In this embodiment, the raw material components include 50 parts of natural graphite, 10 parts of single-walled carbon nanotubes, 4 parts of nano-titanium dioxide, and 20 parts of asphalt coke powder by weight.

[0098] In this embodiment, the speed of the pulverizer in step A is 200 rpm and the pulverizing time is 70 min.

[0099] In this embodiment, the particle size D50 of the natural graphite after sieving in step A is 15 microns, and the tap density is 0.75 g / cm 3 .

[0100] In this embodiment, the stirring and mixing rate in step B is 300 rpm and the mixing time is 40 min.

[0101] In this embodiment, the pre-carbonization temperature in step D is 700° C. and the time is 2 h.

[0102] In this embodiment, the pre-carbonization temperature in step E is 1200° C. and the time is 4 hours.

[0103] In this embodiment, the inert gas introduced in step D is argon, the argon introduction flow rate is 20 L / h, and the introduction time is 70 min.

[0104] In this embodiment, the inert gas introduced in step E is argon, the argon introduction flow rate is 30 L / h, and the introduction time is 130 min.

[0105] Embodiment six:

[0106] A method for preparing a high-capacity natural graphite-based negative electrode material, the preparation method comprising the following steps:

[0107] A. Add natural graphite into a pulverizer for pulverization and then sieve to obtain graphite powder;

[0108] B. Mixing graphite powder with single-walled carbon nanotubes, nano-titanium dioxide and asphalt coke micropowder, immersing in an ethanol solution and stirring to mix;

[0109] C. Then, the solvent is completely evaporated to obtain a mixture;

[0110] D. Add the mixture into a carbonization furnace, and then pass an inert gas to perform pre-carbonization, and obtain a pre-carbonized product after the pre-carbonization is completed;

[0111] E. Carbonizing the pre-carbonized product after heating and protecting it with inert gas to obtain a carbonized product after the carbonization is completed;

[0112] F. After cooling the carbonized product, a graphite-based negative electrode material is obtained.

[0113] In this embodiment, the raw material components include 65 parts of natural graphite, 8 parts of single-walled carbon nanotubes, 6 parts of nano-titanium dioxide, and 15 parts of asphalt coke powder by weight.

[0114] In this embodiment, the speed of the pulverizer in step A is 400 rpm and the pulverizing time is 60 min.

[0115] In this embodiment, the particle size D50 of the natural graphite after sieving in step A is 18 microns, and the tap density is 0.60 g / cm 3 .

[0116] In this embodiment, the stirring and mixing rate in step B is 450 rpm and the mixing time is 30 min.

[0117] In this embodiment, the pre-carbonization temperature in step D is 750° C. and the time is 2 h.

[0118] In this embodiment, the pre-carbonization temperature in step E is 1250° C. and the time is 3 hours.

[0119] In this embodiment, the inert gas introduced in step D is argon, the argon introduction flow rate is 25 L / h, and the introduction time is 60 min.

[0120] In this embodiment, the inert gas introduced in step E is argon, the argon introduction flow rate is 35 L / h, and the introduction time is 100 min.

[0121] Experimental example:

[0122] The negative electrode materials prepared in various embodiments of the present invention were used to perform performance tests, and the data obtained are shown in the following table:

[0123]

[0124]

[0125] The preparation method adopted by the present invention is simple to operate, and the prepared negative electrode material has good conductivity, reduces the impedance of the battery, and effectively enhances the conductivity and electrochemical reaction performance of the product; the present invention first performs pre-carbonization and then performs carbonization, which can effectively prevent the particle powder from bonding to cause agglomeration and affect the processing quality of the negative electrode material; in the present invention, argon gas is introduced during the pre-carbonization and carbonization processes, which can solve the radial and axial segregation problems of the material during the solidification process and improve the processing quality of the negative electrode material.

[0126] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a high-capacity natural graphite-based negative electrode material, characterized in that: The preparation method comprises the following steps: A. Add natural graphite into a pulverizer for pulverization and then sieve to obtain graphite powder; B. Mixing graphite powder with single-walled carbon nanotubes, nano-titanium dioxide and asphalt coke micropowder, immersing in an ethanol solution and stirring to mix; C. Then, the solvent is completely evaporated to obtain a mixture; D. Add the mixture into a carbonization furnace, and then pass an inert gas to perform pre-carbonization, and obtain a pre-carbonized product after the pre-carbonization is completed; E. Carbonizing the pre-carbonized product after heating and protecting it with inert gas to obtain a carbonized product after the carbonization is completed; F. After cooling the carbonized product, a graphite-based negative electrode material is obtained.

2. The method for preparing a high-capacity natural graphite-based negative electrode material according to claim 1, characterized in that: The raw material components include 50-80 parts of natural graphite, 5-10 parts of single-walled carbon nanotubes, 4-8 parts of nano titanium dioxide, and 10-20 parts of asphalt coke powder by weight.

3. The method for preparing a high-capacity natural graphite-based negative electrode material according to claim 1, characterized in that: In step A, the rotation speed of the pulverizer is 200-600 rpm, and the pulverization time is 50 min-70 min.

4. The method for preparing a high-capacity natural graphite-based negative electrode material according to claim 1, characterized in that: In step A, the particle size D50 of the natural graphite after sieving is 15-20 microns, and the tap density is 0.55-0.75 g / cm 3 .

5. The method for preparing a high-capacity natural graphite-based negative electrode material according to claim 1, characterized in that: In step B, the stirring and mixing rate is 300-600 rpm, and the mixing time is 20 min-40 min.

6. The method for preparing a high-capacity natural graphite-based negative electrode material according to claim 1, characterized in that: In the step D, the pre-carbonization temperature is 700-800° C. and the time is 1 h-2 h.

7. The method for preparing a high-capacity natural graphite-based negative electrode material according to claim 1, characterized in that: In the step E, the pre-carbonization temperature is 1200-1300° C. and the time is 2 h-4 h.

8. The method for preparing a high-capacity natural graphite-based negative electrode material according to claim 1, characterized in that: The inert gas introduced in the step D is argon, the argon introduction flow rate is 20-30 L / h, and the introduction time is 50 min-70 min.

9. The method for preparing a high-capacity natural graphite-based negative electrode material according to claim 1, characterized in that: The inert gas introduced in step E is argon, the argon introduction flow rate is 30-40 L / h, and the introduction time is 90 min-130 min.